Peran Kolaborasi dalam Perguruan Tinggi - Rahmawati, Aulia; S, Rinny; Rahmi, Sri (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This research aims to analyze the role of collaboration between universities in improving the quality of education and research. This research uses a literature review method by collecting data through in-depth analysis of various relevant and reliable sources, such as scientific journals, academic books, research articles and other documents that support the research topic. The data analysis process uses a qualitative descriptive approach, where the collected data is analyzed by identifying main themes, patterns and key concepts from the literature reviewed. The results of the analysis show that collaboration in higher education is an important strategy in improving the quality of education and research. Based on the analysis that has been carried out, it can be concluded that collaboration between universities is proven to have a significant role in improving the quality of education and relevance of research. Through partnerships, universities can share resources, such as facilities, experts and knowledge, which have a positive impact on academic development and graduate competency.